Pendampingan Para Petani Walet Melalui Penerapan Brand and Communication Marketing Oleh Markas Walet - Ali Haydar; Augustin Mustika Chairil (FKIP, Universitas Palangka Raya, 2023)
Mentoring has become one of the important factors in improving the quality of knowledge and marketing for swallow farmers. The research aims to explore the assistance of swallow farmers through the application of Brand and Communication Marketing by the Swallow Headquarters in increasing the knowledge and marketing of swallow farmers. In the context of sales, brand assistance and communication marketing help swallow farmers in increasing sales of their swallow products. With the right communication strategy, they can communicate the benefits, value, and uniqueness of swallow products to potential consumers, which in turn drives consumer interest and influences purchasing decisions. In addition, this assistance also expands the market reach of swallow farmers and helps them in building stronger relationships with consumers through relevant communication channels.